No Escape II: The Way Forward. Bringing climate solutions to the frontlines of conflict and displacement - Birner, J.; Eid, J.; O’Keeffe, E.; Yonetani, M. (United Nations High Commissioner for Refugees, 2025)
This report shows that an evidence-based, whole-of-society approach that allows all to participate and leaves no one behind is both possible and essential. By aligning climate, humanitarian, and development action, and – critically – ensuring accessible and inclusive finance, we can help frontline communities withstand today’s shocks and share in a resilient future. Here, the engagement of the private sector is also vital – from the start, and into the future – bridging innovation, investment and inclusive solutions for resilience and adaptation.